Color removal from textile wastewater using date seeds activated carbon (Bangladesh Journal of Scientific and Industrial Research, 2017)
Powdered Activated carbon (PAC) developed from date seeds was used as an adsorbent for the removal of color from textile wastewater. Batch adsorption experiments were performed in the laboratory with varying process parameters (temperature, pH, agitation, adsorbent dosage, particle size) over a range of contact periods and wastewater pollutant (color) levels. It was found that the removal mechanism could be better characterized by the Freundlich adsorption isotherm model compared to the Langmuir model. Also, The Lagergren's pseudo 2nd order kinetic model fitted relatively well ( = 0.99) over the selected range of contact times (5-60 minutes) and initial color concentrations (800-1200 Pt-Co unit) compared to the pseudo-first order model indicating that chemisorption may be playing a dominant role in the adsorption process. Both external film and intra-particle pore diffusion mechanism were involved in the adsorption process but film diffusion was found to be rate limiting. While analyzing the thermodynamics, the negative value of free energy (-1.83 to -3.4 KJ/mole), positive value of enthalpy (0.26 to 0.28 KJ/mole) and entropy (0.97 to 1.01 J/K/Mole) associated with the color removal mechanism indicated that adsorption was spontaneous and endothermic with increased disorder and randomness at the solid-liquid interface of the date seeds PAC. These experiments suggests that date seeds PAC is a very effective adsorbent, capable of removing a significant amount of color from industrial wastewater if process variables can be optimized and can be explored as a potential low-cost alternative to expensive tertiary treatment options.Bangladesh J. Sci. Ind. Res. 52(1), 31-42, 2017